(untitled) (Interdisciplinary Studies Journal, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that involves specific difficulties, primarily in social and communicative skills. For many years, autism has been surrounded by pejorative stigmas that underestimated its intellectual and cognitive capacities. In this context, the aim of this study is to describe the knowledge of parents and teachers at an urban public elementary school in the Federal District regarding ASD. This is a quantitative study, involving the development and validation of a data collection instrument consisting of 30 questions, designed to assess beliefs and general knowledge about ASD. A total of 63 parents and 26 teachers of students aged 6 to 12 years, who had limited prior contact with ASD, were interviewed. Among the parents, 68.2% considered their knowledge about ASD insufficient, while 66.7% of the teachers also evaluated their knowledge as inadequate. Regarding certain beliefs, 12.7% of parents believed that ASD could be cured, whereas none of the teachers shared this view. Therefore, this study demonstrates that stigmas related to ASD still exist and highlights the need for health education initiatives regarding this disorder within both school and community contexts.